2017
DOI: 10.1002/aic.15809
|View full text |Cite
|
Sign up to set email alerts
|

Transitional flow in a Rushton turbine stirred tank

Abstract: The way in which the single phase flow of Newtonian liquids in the vicinity of the impeller in a Rushton turbine stirred tank goes through a laminar -turbulent transition has been studied in detail experimentally (with Particle Image Velocimetry, PIV) as well as computationally. For Reynolds numbers equal to or higher than 6,000, the average velocities and velocity fluctuation levels scale well with the impeller tip speed, i.e. show Reynolds independent behavior. Surprising flow structures were measured -and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
3
16
0
1
Order By: Relevance
“…This implies that for this vessel configuration, turbulent conditions (i.e., constant mixing number) are reached at relatively low Reynolds ( Re = 5,400). This seems to be consistent with the results obtained by Zhang et al, 29 who found Reynolds independent flow behaviour for Re > 6,000 in a small sized stirred tank vessel ( T = 28.5 cm) equipped with a Rushton Turbine impeller. Similarly, Machado et al 30,31 also showed low Re associated to turbulent flow regimes for both axial and radial flow impeller types.…”
Section: Resultssupporting
confidence: 93%
“…This implies that for this vessel configuration, turbulent conditions (i.e., constant mixing number) are reached at relatively low Reynolds ( Re = 5,400). This seems to be consistent with the results obtained by Zhang et al, 29 who found Reynolds independent flow behaviour for Re > 6,000 in a small sized stirred tank vessel ( T = 28.5 cm) equipped with a Rushton Turbine impeller. Similarly, Machado et al 30,31 also showed low Re associated to turbulent flow regimes for both axial and radial flow impeller types.…”
Section: Resultssupporting
confidence: 93%
“…Although these studies do not focus particularly on the underlying nature of the transitional flow, but rather specific mixing applications, the results demonstrate that moderate Reynolds numbers allow the flow ta be simulated directly, without the use of a turbulence clo sure or subgrid-scale models. Although, in their recent study, Zhang et al (2017) have shown that even for simple Newtonian flows, ONS failed ta correctly predict the flow patterns and velocity fluctuation levels at certain transitional Reynolds numbers. Their work also shows the current state of confusion in modeling transitional flows as they attempted ta apply transition models developed for externat aerody namics ta internai flow and performed fini te volume simulations using 2nd order upwind differencing that they erroneously called finite vol ume ONS.…”
Section: Introductionmentioning
confidence: 96%
“…Ultimately, the full resolution of the time-dependent Navier-Stokes equations on an extremely fine 3-dimensional mesh would be desirable however such simulations require excessive com puting efforts, which may not be viable for practical engineering applications. As a result, there are very few studies in the literature that deal with the simulation of transitional flow in stirred tanks and almost ail of the available literature may be attributed ta a single author (Derksen, 2011(Derksen, , 2012a(Derksen, , 2012b(Derksen, , 2013Zhang et al, 2017). In his studies, Derksen has used the Lattice Boltzmann method ta perform direct numerical simulations (ONS) of flows with Reynolds numbers in the range 2000-12000.…”
Section: Introductionmentioning
confidence: 99%
“…8, the axial distribution of dimensionless velocity at the same Reynolds number is almost coincidence with different working media for laminar and turbulent regimes. Recently, Zhang et al (2017) found that liquids with different viscosity but stirred at the same Reynolds number generated the same dimensionless velocity fields although in transitional flow regime.…”
Section: Model Validationmentioning
confidence: 99%